ENTREPRENEURSHIP AS THE MAIN COMPONENT OF ECONOMIC ACTIVITY IN THE STATE - Клименко, Наталія (SWorldJournal, 2022)
The paper considers the differences in the legal regulation of business activities in terms of economic law.